Molecular sieve confinement noble metal catalyst for CO-SCR denitration as well as preparation method and application of molecular sieve confinement noble metal catalyst

By encapsulating Ir metal nanoclusters in the domain-limited domain of the molecular sieve, the problems of low utilization rate and poor stability of existing Ir-based catalysts are solved, and efficient CO-SCR denitrification catalytic effect and good industrial application potential are achieved.

CN119406447AActive Publication Date: 2025-02-11INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411538482.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

During the CO-SCR denitrification process, existing Ir-based catalysts have problems such as low utilization of active metals, difficult adjustment of active sites, poor oxygen and sulfur resistance, and poor catalyst stability, which limits their further development in industrial applications.

Method used

Through the in-situ synthesis-ligand protection one-pot hydrothermal method, the domain-limited encapsulation of Ir metal nanoclusters inside the molecular sieve, optimizing the utilization rate of metals and the stability of the catalyst. This method controls the synergistic effect of Irδ+ and Ir0 to improve catalytic activity by regulating the proportion of ligands and the type of molecular sieve.

Benefits of technology

The efficient catalytic activity and stability of the catalyst are achieved, the problem of low stability of single metal catalysts is overcome, and it has excellent industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406447A_ABST
    Figure CN119406447A_ABST
Patent Text Reader

Abstract

The invention discloses a molecular sieve confinement noble metal catalyst for CO-SCR denitration as well as a preparation method and application thereof, and belongs to the technical field of catalytic reduction of nitrogen oxides. The catalyst comprises a molecular sieve carrier and an Ir metal nanocluster loaded in the molecular sieve carrier through confinement encapsulation. The preparation method comprises the following steps: mixing a first metal precursor solution with a first ligand to obtain a first mixed solution; mixing a second metal precursor solution with a second ligand to obtain a second mixed solution; mixing a silicon source, an aluminum source, alkali and a solvent to obtain a molecular sieve precursor solution; and mixing the molecular sieve precursor solution with the first mixed solution, then adding the second mixed solution, carrying out a hydrothermal crystallization reaction, and then carrying out centrifugal washing, drying and calcining to obtain the catalyst. The catalyst has good stability, shows a high nitrogen oxide conversion rate in an atmosphere containing O2 and SO2, and improves the catalytic ability of the catalyst to nitrogen oxides under different conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic reduction of nitrogen oxides, and in particular to a molecular sieve confined noble metal catalyst for CO-SCR denitration, and a preparation method and application thereof. Background Art

[0002] The sources of anthropogenic nitrogen oxides are mainly concentrated in vehicle exhaust emissions, power plants and industrial waste gas emissions. Nitrogen oxides not only cause harm to the environment, but also have potential harm to human health and ecosystems. Therefore, it is necessary to control nitrogen oxides (NO x ) is extremely important. Currently, the main technology for controlling nitrogen oxides is NH3-SCR technology, which uses NH3 as a reducing agent to selectively convert nitrogen oxides into harmless N2 via a catalyst. However, NH3 can cause ammonia slip and secondary pollution. Therefore, CO-SCR technology, which uses CO already in the flue gas as a reducing agent, is gaining increasing attention. This technology offers advantages such as low secondary pollution and simple operation.

[0003] The problem that needs to be solved when CO-SCR catalyst is put into industrial application is that O2 and SO2 in the flue gas will cause the catalyst to deactivate. Studies have shown that Ir-based catalysts have higher activity than other catalysts under oxygen-containing conditions. When Ir is used as an active metal, the main function is the oxidation state of Ir. δ+ Site and metallic Ir 0 The high catalytic activity of Ir-based catalysts for CO-SCR reaction is mainly due to Ir δ+ With Ir 0 The synergistic effect is achieved, in which the oxidation state of Ir δ+ It is easier to selectively adsorb NO, then form ONNO intermediates, and then overflow to the adjacent Ir 0 Thus reacting with CO to form N2. A certain proportion of oxidized Ir δ+ Site and metallic Ir 0 Can improve reactivity.

[0004] However, the Ir-based catalysts in the existing technology have problems such as low active metal utilization, difficult adjustment of active sites, poor oxygen and sulfur resistance, and poor catalyst stability, which limit the further application of Ir-based catalysts. How to improve these problems and provide Ir-based catalysts with better performance has become a difficult problem that technicians in this field urgently need to overcome. Summary of the Invention

[0005] The purpose of the present invention is to provide a molecular sieve confined precious metal catalyst for CO-SCR denitrification, and its preparation method and application, in order to solve the problems existing in the above-mentioned prior art. The present invention introduces metals into the molecular sieve synthesis through a one-pot hydrothermal method of in-situ synthesis-ligand protection, uses ligands to guide the anchoring of metal nanoclusters inside the molecular sieve, and accelerates the formation of the molecular sieve structure. The catalyst preparation method proposed in the present invention is simple to operate and shortens the preparation time; in the preparation method, only water is used as a solvent, which reduces the emission of harmful substances. The molecular sieve carrier of the prepared catalyst has high hydrothermal stability, and the occurrence state of the active component is adjustable, which optimizes the utilization rate of the metal and enhances the stability and catalytic activity of the catalyst in harsh environments.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention: a molecular sieve confined precious metal catalyst for CO-SCR denitrification, wherein the molecular sieve confined precious metal catalyst includes a molecular sieve carrier and Ir metal nanoclusters loaded in the molecular sieve carrier by confined encapsulation (Ir metal nanoclusters serve as the active component of the catalyst).

[0008] That is, the catalyst is a molecular sieve that confines and encapsulates Ir metal nanoclusters.

[0009] Furthermore, the molecular sieve carrier is type A molecular sieve, type X molecular sieve or type Y molecular sieve; the loading amount of the Ir metal nanoclusters in the molecular sieve confined noble metal catalyst is 0.1 to 1 wt.%; and the particle size of the Ir metal nanoclusters is ≤2 nm.

[0010] Furthermore, the Ir metal nanoclusters include Ir metal nanoclusters with a particle size of less than 0.8 nm and Ir metal nanoclusters with a particle size of 1 to 2 nm.

[0011] Furthermore, the Ir metal nanoclusters include oxidized Ir δ+ and metallic Ir 0 , where Ir 0 The proportion is 10~70wt.%.

[0012] Furthermore, the molecular sieve has a cage-like structure and is rich in aluminum hydroxyl and silicon hydroxyl sites.

[0013] The general chemical formula of molecular sieve is M2O·Al2O3·xSiO2·yH2O, where M is a monovalent cation, such as K + 、Na + wait.

[0014] The second technical solution of the present invention: The preparation method of the molecular sieve confined precious metal catalyst for CO-SCR denitrification comprises the following steps:

[0015] Mixing a first metal precursor solution with a first ligand and stirring to obtain a first mixed solution;

[0016] mixing a second metal precursor solution with a second ligand and stirring to obtain a second mixed solution;

[0017] Mixing a silicon source, an aluminum source, an alkali, and a solvent, and stirring to obtain a molecular sieve precursor solution; mixing the molecular sieve precursor solution with the first mixed solution, and stirring, and then adding the second mixed solution, and stirring to obtain a third mixed solution;

[0018] Performing a hydrothermal crystallization reaction on the third mixed liquid, and after the hydrothermal crystallization reaction, centrifugally washing, drying, and calcining to obtain the molecular sieve confined precious metal catalyst for CO-SCR denitrification;

[0019] The first metal precursor solution and the second metal precursor solution are both Ir salt solutions.

[0020] During the preparation process, the type of molecular sieve obtained (i.e., whether the molecular sieve is type A molecular sieve, type X molecular sieve, or type Y molecular sieve) can be controlled by regulating the silicon-aluminum ratio (the molar ratio of the silicon source to the aluminum source) and the hydrothermal crystallization reaction time.

[0021] Furthermore, the concentration of Ir in the first metal precursor solution is 0.1 to 10 g / L; the concentration of Ir in the second metal precursor solution is 0.1 to 10 g / L.

[0022] Furthermore, the first metal precursor solution and the second metal precursor solution have the same concentration.

[0023] Furthermore, the solvent is water.

[0024] Furthermore, the first ligand is a C1-6 straight-chain amine compound; the second ligand is an alkoxysilane containing a mercapto group or an amino group; the solute of the Ir salt solution includes at least one of iridium nitrate, iridium acetate and chloroiridic acid, preferably chloroiridic acid; and the solvent of the Ir salt solution is water.

[0025] Furthermore, the first ligand is preferably at least one of ethylenediamine, 1,3-propylenediamine and mercaptoethylamine, more preferably 1,3-propylenediamine; the second ligand is preferably at least one of (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, more preferably (3-aminopropyl)trimethoxysilane.

[0026] The present invention utilizes the thiol or amino groups on the first and second ligands to bind to the metal precursor (Ir salt). The thiol and amino groups easily coordinate with the metal to form a relatively stable complex, thereby preventing the metal precursor from precipitating in the alkaline environment of molecular sieve synthesis and ensuring its entry into the molecular sieve. The alkoxysilane portion of the second ligand hydrolyzes and combines with the silanol groups of the silicon source and the aluminum hydroxyl groups of the aluminum source to form covalent bonds, promoting the formation of the molecular sieve and the confined encapsulation of the metal nanoclusters.

[0027] Furthermore, the aluminum source includes sodium metaaluminate (NaAlO2), boehmite (AlOOH·nH2O), pseudo-boehmite (AlOOH·nH2O), amorphous aluminum hydroxide powder (Al(OH)3) and aluminum isopropoxide (C9H 21 AlO3), preferably sodium aluminate and / or aluminum isopropoxide; the silicon source includes at least one of water glass (Na2O·nSiO2), silica sol (SiO2·nH2O), silica gel ((C2H6OSi)n) and amorphous SiO2 powder, preferably silica sol and / or silica gel; the alkali is NaOH and / or KOH, preferably NaOH.

[0028] Furthermore, the molar ratio of the Ir salt (i.e., the Ir contained in the Ir salt) to the first ligand in the first mixed solution is 1:3-8; the molar ratio of the Ir salt to the second ligand in the second mixed solution is 1:6-12.

[0029] Furthermore, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali is calculated as Na2O and / or K2O, and the Ir salt is calculated as Ir. The molar ratio of the silicon source, the aluminum source, the alkali, the Ir salt, the first ligand, and the second ligand in the third mixed solution is 1-8:1:1-4:0.003-0.020:0.001-0.16:0.001-0.24. That is, in terms of molar ratio, the reaction system formed by the third mixed solution has a ratio of SiO2:Al2O3:Na2O and / or K2O:Ir:first ligand:second ligand = 1-8:1:1-4:0.003-0.020:0.001-0.16:0.001-0.24.

[0030] Furthermore, the molar ratio of the silicon source, the aluminum source and the solvent (water) in the molecular sieve precursor solution is 1-8:1:100-140.

[0031] Furthermore, the stirring temperature is 20-50°C, preferably 20°C, 25°C, 30°C, 35°C, 40°C or 50°C, more preferably 30°C.

[0032] Furthermore, when the first metal precursor solution is mixed with the first ligand, the stirring time is 0.5 to 2 hours, preferably 0.5 hours, 1 hour, 1.5 hours or 2 hours, and more preferably 0.5 hours; when the second metal precursor solution is mixed with the second ligand, the stirring time is 0.5 to 2 hours, preferably 0.5 hours, 1 hour, 1.5 hours or 2 hours, and more preferably 0.5 hours; when the molecular sieve precursor solution is mixed with the first mixed solution, the stirring time is 0.1 to 1 hour, preferably 0.1 hours, 0.5 hours or 1 hour, and more preferably 0.5 hours; after adding the second mixed solution, the stirring time is 1 to 4 hours, preferably 1 hour, 2 hours, 3 hours or 4 hours, and more preferably 3 hours.

[0033] Furthermore, the specific operation of mixing the silicon source, aluminum source, alkali and solvent and stirring to obtain the molecular sieve precursor solution is: mixing the aluminum source, alkali and half of the solvent and stirring to obtain an aluminum alkali solution; mixing the silicon source with the other half of the solvent and stirring to obtain a silicon source solution; mixing the aluminum alkali solution and the silicon source solution and stirring to obtain the molecular sieve precursor solution.

[0034] Furthermore, the stirring time after mixing the aluminum source, alkali and half of the solvent, the stirring time after mixing the silicon source and the other half of the solvent, and the stirring time after mixing the aluminum alkali solution and the silicon source solution are all 0.1 to 1 h, preferably 0.1 h, 0.5 h or 1 h, and more preferably 0.5 h.

[0035] Furthermore, the temperature of the hydrothermal crystallization reaction is 80-120°C, and the time is 3-48 hours; the temperature of the drying is 80-120°C; the temperature of the calcination is 400-600°C, and the time is 4-8 hours, and the heating rate is 1-10°C / min.

[0036] Furthermore, the temperature of the hydrothermal crystallization reaction is preferably 80°C, 90°C, 100°C, 110°C or 120°C, more preferably 100°C; the time is preferably 3h, 4h, 6h, 12h or 48h, more preferably 4h.

[0037] Furthermore, the drying temperature is preferably 80°C, 90°C, 100°C, 110°C or 120°C, more preferably 100°C.

[0038] Furthermore, the calcination temperature is preferably 400°C, 450°C, 500°C, 550°C or 600°C, more preferably 550°C; the calcination time is preferably 4h, 5h, 6h, 7h or 8h, more preferably 6h; the heating rate is preferably 1°C / min, 2°C / min, 5°C / min or 10°C / min, more preferably 2°C / min.

[0039] Furthermore, after the hydrothermal crystallization reaction is completed, the alkaline solution of the molecular sieve encapsulating Ir metal nanoclusters is obtained, and the rotation speed of the centrifugal washing is 4000-10000 rpm, preferably 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm or 10000 rpm, more preferably 4000 rpm.

[0040] Furthermore, the number of centrifugal washing is 3 to 5 times.

[0041] Furthermore, the time for each centrifugal washing is 5 to 10 min, preferably 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, more preferably 5 min.

[0042] Furthermore, the temperature of the centrifugal washing is room temperature, the solvent is water, and the pH of the precipitate after centrifugal washing is 8-10.

[0043] During the centrifugal washing process, excess alkali and other impurities are washed away, leaving behind pure catalyst precipitates.

[0044] Furthermore, the drying is performed in an air atmosphere.

[0045] Furthermore, the calcination is carried out in an air atmosphere.

[0046] The present invention uses a method in which a dual ligand is first separately combined with a metal precursor solution to obtain a first mixed solution and a second mixed solution, which is then added stepwise to a molecular sieve precursor solution for mixing. The dual ligand is first separately combined with the metal precursor solution so that the metal ions are fully combined with the ligands in the subsequent process to complete the initial formation of metal nanoclusters; through the mixed reaction of the molecular sieve precursor solution with the first mixed solution and the second mixed solution, an A, X or Y type molecular sieve is generated, and the complex formed by the ligand and the metal ion enters the crystallizing A, X or Y type molecular sieve, and the alkoxysilane part of the ligand is combined with the silanol of the silicon source or the aluminum hydroxyl of the aluminum source to form a Si-O-Si bond or a Si-O-Al bond, thereby accelerating the formation of the molecular sieve crystal structure. During the centrifugal washing process, impurities such as excess alkali are washed away, leaving a pure catalyst precipitate. After calcination under dry, high-temperature air conditions, substances such as the ligand are fully decomposed to obtain an A, X or Y molecular sieve catalyst that confines and encapsulates Ir metal clusters. The preparation process of the catalyst is simple, easy to operate, and has low environmental pollution.

[0047] The first ligand in the dual ligand is a C1-6 linear amine compound, and the second ligand is an alkoxysilane containing either a thiol or amino group. The first ligand is relatively small and flexible. The lone electron pair on the nitrogen atom of the amino group forms a coordination bond with the metal ion, guiding the metal into the small pores of the molecular sieve. The second ligand is a larger, branched bifunctional ligand, preferentially occupying the large pores or supercage structure of the molecular sieve. The sulfur element in the thiol group and the nitrogen element in the amino group of the second ligand have high electronegativity and a strong affinity for positively charged metal ions, thus preferentially binding to them. The alkoxysilane portion of the bifunctional ligand bonds with the silanol group of the silicon source and the alumol group of the aluminum source, forming Si-O-Si or Si-O-Al bonds, accelerating the formation of the molecular sieve structure. The size of the metal clusters in the synthesized catalyst is influenced by the ratio of the ligands and the cage or pore size of the molecular sieve, primarily limited to <0.8 nm and 1-2 nm, achieving low metal loading while optimizing metal utilization.

[0048] The third technical solution of the present invention: the application of the above-mentioned molecular sieve confined precious metal catalyst for CO-SCR denitrification in catalyzing the selective reduction of nitrogen oxides by carbon monoxide (CO) in fixed source flue gas or mobile source exhaust gas (i.e., application in CO-SCR reaction).

[0049] Furthermore, the nitrogen oxides in the fixed source flue gas or mobile source exhaust gas include NO (the molecular sieve confined precious metal catalyst used for CO-SCR denitrification plays a selective catalytic reduction role on NO in nitrogen oxides); the fixed source flue gas and / or mobile source exhaust gas also contains O2 and SO2.

[0050] Furthermore, the concentration of NO in the fixed source flue gas or mobile source exhaust gas is 50 to 500 ppm, preferably 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 400 ppm or 500 ppm, and more preferably 400 ppm.

[0051] Furthermore, the concentration of CO in the fixed source flue gas or mobile source tail gas is 400 to 10000 ppm, preferably 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm or 1000 ppm, and more preferably 400 ppm.

[0052] Furthermore, the concentration of O2 in the fixed source flue gas or mobile source exhaust gas is 0 to 15 vol.%, and is not 0; the concentration of SO2 in the fixed source flue gas or mobile source exhaust gas is 0 to 400 ppm, and is not 0.

[0053] Furthermore, the concentration of O2 in the fixed source flue gas or mobile source exhaust gas is preferably 1 vol.%, 2 vol.%, 3 vol.%, 4 vol.%, 5 vol.%, 10 vol.% or 15 vol.%, and more preferably 5 vol.%; the concentration of SO2 in the fixed source flue gas or mobile source exhaust gas is preferably 50 ppm, 100 ppm, 200 ppm, 300 ppm or 400 ppm, and more preferably 100 ppm.

[0054] Furthermore, the reaction temperature of the molecular sieve confined precious metal catalyst for CO-SCR denitrification catalyzing the selective reduction of nitrogen oxides by carbon monoxide in fixed source flue gas or mobile source exhaust gas is 150-400°C, preferably 150°C, 200°C, 250°C, 300°C, 350°C or 400°C.

[0055] Furthermore, before the catalyst is used to catalyze the selective reduction of nitrogen oxides by carbon monoxide in fixed source flue gas or mobile source exhaust gas (i.e., before the CO-SCR reaction), it also includes pretreatment of the catalyst, specifically: pretreating the catalyst in a H2 / N2 mixed atmosphere at 200°C for 20 to 60 minutes, wherein the proportion of hydrogen in the H2 / N2 mixed atmosphere is 1 to 10 vol.%, preferably 1 vol.%, 2 vol.%, 3 vol.%, 4 vol.%, 5 vol.% or 10 vol.%, and more preferably 5 vol.%.

[0056] Furthermore, the pretreatment time is preferably 20 min, 30 min, 40 min, 50 min or 60 min, more preferably 30 min.

[0057] The present invention provides a catalyst for the selective catalytic reduction of nitrogen oxides, a preparation method and an application thereof. By confining and encapsulating Ir metal nanoclusters within a molecular sieve, the present invention solves the problems of low active metal utilization, difficulty in adjusting active sites, poor oxygen and sulfur resistance, and poor catalyst stability in the current catalysts for the selective catalytic reduction of nitrogen oxides. It also solves the problems of a complex catalyst preparation process, a long preparation cycle, and high costs. The resulting catalyst has improved catalytic activity and stability, and has broad application prospects.

[0058] In Ir-based catalysts, a certain proportion of oxidized Ir δ+ Site and metallic Ir 0 The reaction activity can be improved. The present invention controls the proportion of the two valence states of Ir by the particle size and distribution of Ir metal nanoclusters. The larger the cluster particles, the higher the proportion of metallic Ir. 0 The higher the proportion. The present invention uses an in-situ synthesis method to limit the encapsulation of clusters inside the molecular sieve, which can effectively control the particle size and dispersion of metal clusters. A, X or Y type molecular sieve is a material with a uniform pore structure and high crystallinity, with the characteristics of high specific surface area, excellent hydrothermal stability and chemical stability, etc., as a carrier for anchoring and dispersing metal active sites. The framework structure of A, X or Y type molecular sieve is composed of silicon oxide tetrahedron and aluminum oxide tetrahedron. On the basis of silicon oxide tetrahedron and aluminum oxide tetrahedron, three-dimensional β cage and α cage structure are further formed to accommodate metal clusters. The present invention uses two different ligands to introduce Ir clusters into different sites in the molecular sieve in steps to regulate the size and distribution of Ir clusters. The geometric configuration and size of the first ligand make it tend to build clusters in smaller pores in the molecular sieve (<0.8nm), while the size of the second ligand makes it build larger clusters (1-2nm) in the super cage of the molecular sieve.

[0059] Ir-based catalysts during the reaction 0 Easily oxidized to Ir by O2 δ+ , leading to Ir δ+ With Ir 0 The balance of Ir is destroyed, the synergistic effect is reduced, and the reaction activity is reduced. The presence of SO2 in the flue gas can promote the δ+ Xiang Ir 0 Different concentrations of SO2 have different effects. Under the combined action of O2 and SO2, Ir δ+ With Ir 0 Therefore, the Ir content introduced by the first ligand and the second ligand can be adjusted for flue gases with different O2:SO2 ratios, thereby regulating the size of the clusters.

[0060] The present invention discloses the following technical effects:

[0061] (1) The molecular sieve confined noble metal catalyst designed in the present invention for CO-SCR denitrification realizes the regulation of the proportion of different occurrence states of active sites, thereby improving the selective catalytic reduction ability of the metal sites for nitrogen oxides.

[0062] (2) The present invention adopts a one-pot hydrothermal method of in situ synthesis-ligand protection to prepare the catalyst. During the synthesis process, metal clusters with different particle sizes are introduced by adding two ligands in steps. The method is easy to operate, has a short preparation time, and has the potential for large-scale industrial application. The product of the complete catalytic reduction of nitrogen oxides is nitrogen gas, which is beneficial to reducing environmental pollution.

[0063] (3) The molecular sieve confined precious metal catalyst for CO-SCR denitrification prepared by the present invention has excellent catalytic activity, which is significantly improved compared with the catalytic activity of existing catalysts, and overcomes the problem of low stability of general single metal catalysts, and has excellent potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0065] Figure 1 The XRD spectra of the catalysts prepared in Example 3 and Comparative Example 1 are shown;

[0066] Figure 2 TEM image of the catalyst prepared in Example 3;

[0067] Figure 3 The particle size distribution diagram of Ir nanoclusters in the catalysts prepared in Examples 1 to 3 and Comparative Examples 2 to 3;

[0068] Figure 4 This is a diagram showing the stability test results of the catalyst prepared in Example 3. DETAILED DESCRIPTION

[0069] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0070] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0071] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0072] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.

[0073] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0074] If no specific techniques or conditions are specified in the embodiments of the present invention, the methods shall be carried out in accordance with conventional techniques or conditions in the art or in accordance with the product instructions. Raw materials or instruments used without manufacturer specified are conventional products commercially available through regular channels.

[0075] The room temperature involved in the specific implementation manner of the present invention specifically refers to 20-30°C.

[0076] The Ir salt (metal precursor), first ligand, second ligand, aluminum source, silicon source and base involved in the specific embodiment of the present invention can be equally replaced within the scope defined by the present invention without affecting the realization of the technical effect.

[0077] Example 1

[0078] A type A molecular sieve confined precious metal catalyst for CO-SCR denitrification, the preparation steps are as follows:

[0079] S1. Dissolve 1 g of chloroiridic acid hexahydrate (with an Ir content of 39 wt.%) in water to prepare 100 mL of chloroiridic acid solution (with an Ir concentration of 3.9 g / L); (as the first metal precursor solution and the second metal precursor solution);

[0080] S2. Take 8.50 mL of chloroiridic acid solution (wherein Ir is 0.033 g, i.e., 0.172 mmol) (first metal precursor solution) and mix it with 0.08 g (1.1 mmol) of 1,3-propylenediamine (first ligand), and stir at 30° C. for 0.5 h to obtain a first mixed solution;

[0081] S3. Take 2.80 mL of chloroiridic acid solution (wherein Ir is 0.011 g, i.e., 0.057 mmol) (second metal precursor solution) and mix it with 0.065 g (0.4 mmol) of (3-aminopropyl)trimethoxysilane (second ligand), and stir at 30° C. for 0.5 h to obtain a second mixed solution;

[0082] S4, take 1.2g (0.03mol) of sodium hydroxide (alkali) and 2.5g (0.03mol) of sodium metaaluminate (aluminum source) and dissolve them in 12mL (0.67mol) of deionized water, and stir at 30°C for 0.5h to obtain an aluminum alkali solution; take 6g (wherein the SiO2 content is 30wt.%, i.e., containing SiO20.03mol) of silica sol (silicon source) and mix it with 15mL (0.83mol) of deionized water, and stir at 30°C for 0.5h to obtain a silicon source solution; mix the aluminum alkali solution and the silicon source solution, and stir at 30°C for 0.5h to obtain a molecular sieve precursor solution; mix the molecular sieve precursor solution with the first mixed solution, stir at 30°C for 0.5h, then add the second mixed solution, and continue stirring at 30°C for 3h to obtain a third mixed solution;

[0083] S5, hydrothermally crystallizing the third mixed solution at 100° C. for 4 h to obtain a suspension;

[0084] S6. Using water as the centrifugal washing solvent, the suspension was centrifugally washed 5 times at a centrifugal speed of 4000 rpm, and the centrifugal washing time for each time was 5 min. The solid product obtained by centrifugal washing (the pH value was 8-10 as detected by pH test paper) was dried in an air atmosphere at 100°C, and then ground in a mortar for 5 min. The ground sample was calcined in an air atmosphere at 550°C for 6 h at a heating rate of 2°C / min to obtain a type A molecular sieve confined precious metal catalyst for CO-SCR denitrification (according to ICP testing, the Ir loading amount in the catalyst prepared in this embodiment was 0.83 wt.%).

[0085] Example 2

[0086] Compared with Example 1, the difference is that the amounts of the first metal precursor solution, the second metal precursor solution, the first ligand and the second ligand are 5.6 mL, 5.6 mL, 0.053 g and 0.13 g, respectively (according to ICP testing, the Ir loading amount in the catalyst prepared in this example is 0.81 wt.%).

[0087] Example 3

[0088] Compared with Example 1, the difference is that the amounts of the first metal precursor solution, the second metal precursor solution, the first ligand and the second ligand are 2.8 mL, 8.5 mL, 0.027 g and 0.194 g, respectively (according to ICP testing, the Ir loading amount in the catalyst prepared in this example is 0.79 wt.%).

[0089] Comparative Example 1

[0090] The preparation steps of pure type A molecular sieve are as follows:

[0091] 1.2 g of sodium hydroxide and 2.5 g of sodium aluminate were dissolved in 12 mL of deionized water and stirred at 30° C. for 0.5 h to obtain an aluminum base solution; 6 g of silica sol was mixed with 15 mL of deionized water and stirred at 30° C. for 0.5 h to obtain a silicon source solution; the silicon aluminum base solution and the silicon source solution were mixed and stirred at 30° C. for 0.5 h to obtain a molecular sieve precursor solution; the molecular sieve precursor solution was hydrothermally crystallized at 100° C. for 4 h, and then water was used as a centrifugal washing solvent to centrifuge the hydrothermal crystallization reaction product 5 times at a centrifugal speed of 4000 rpm and a centrifugal washing time of 5 min each time; the centrifugal washing product was then placed in an air atmosphere at 100° C. to dry, and then ground for 5 min, and the ground sample was calcined at 550° C. in an air atmosphere for 6 h at a heating rate of 2° C. / min to obtain pure type A molecular sieve.

[0092] Comparative Example 2

[0093] The steps for preparing the catalyst are as follows:

[0094] S1. Dissolve 1 g of chloroiridic acid hexahydrate (with an Ir content of 39 wt.%) in water to prepare 100 mL of chloroiridic acid solution;

[0095] S2. Mix 11.50 mL of chloroiridic acid solution with 0.10 g of 1,3-propylenediamine, and stir at 30° C. for 0.5 h to obtain a first mixed solution;

[0096] S3, take 1.2g sodium hydroxide (alkali) and 2.5g sodium aluminate (aluminum source) and dissolve them in 12mL deionized water, stir at 30℃ for 0.5h to obtain an aluminum alkali solution; take 6g silica sol (silicon source) and mix it with 15mL deionized water, stir at 30℃ for 0.5h to obtain a silicon source solution; mix the aluminum alkali solution and the silicon source solution, stir at 30℃ for 0.5h to obtain a molecular sieve precursor solution; mix the molecular sieve precursor solution with the first mixed solution, stir at 30℃ for 3h to obtain a second mixed solution;

[0097] S4, hydrothermally crystallizing the second mixed solution at 100° C. for 4 h to obtain a suspension;

[0098] S5. Using water as the centrifugal washing solvent, the suspension was centrifugally washed 5 times at a centrifugal speed of 4000 rpm, and the centrifugal washing time for each time was 5 min. The solid product obtained by centrifugal washing (the pH value was 8-10 as detected by pH test paper) was then dried in an air atmosphere at 100°C, and then ground in a mortar for 5 min. The ground sample was calcined in an air atmosphere at 550°C for 6 h at a heating rate of 2°C / min to obtain a catalyst (according to ICP testing, the Ir loading amount in the catalyst prepared in this embodiment was 0.80 wt.%).

[0099] Comparative Example 3

[0100] S1. Dissolve 1 g of chloroiridic acid hexahydrate (with an Ir content of 39 wt.%) in water to prepare 100 mL of chloroiridic acid solution;

[0101] S2. Mix 11.50 mL of chloroiridic acid solution with 0.258 g of (3-aminopropyl)trimethoxysilane, and stir at 30° C. for 0.5 h to obtain a first mixed solution;

[0102] S3, take 1.2g sodium hydroxide (alkali) and 2.5g sodium aluminate (aluminum source) and dissolve them in 12mL deionized water, stir at 30℃ for 0.5h to obtain an aluminum alkali solution; take 6g silica sol (silicon source) and mix it with 15mL deionized water, stir at 30℃ for 0.5h to obtain a silicon source solution; mix the aluminum alkali solution and the silicon source solution, stir at 30℃ for 0.5h to obtain a molecular sieve precursor solution; mix the molecular sieve precursor solution with the first mixed solution, stir at 30℃ for 3h to obtain a second mixed solution;

[0103] S4, hydrothermally crystallizing the second mixed solution at 100° C. for 4 h to obtain a suspension;

[0104] S5. Using water as the centrifugal washing solvent, the suspension was centrifugally washed 5 times at a centrifugal speed of 4000 rpm, and the centrifugal washing time for each time was 5 min. The solid product obtained by centrifugal washing (the pH value was 8-10 as detected by pH test paper) was then dried in an air atmosphere at 100°C, and then ground in a mortar for 5 min. The ground sample was calcined in an air atmosphere at 550°C for 6 h at a heating rate of 2°C / min to obtain a catalyst (according to ICP testing, the Ir loading amount in the catalyst prepared in this embodiment was 0.83 wt.%).

[0105] Effect verification

[0106] 1. XPS test

[0107] XPS test was performed on the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 to detect Ir δ+ With Ir 0 The results are shown in Table 1.

[0108] Table 1

[0109]

[0110] According to the data in Table 1, the active site Ir 0 With Ir δ+ It can be seen that with the change of the amount of the first metal precursor solution, the second metal precursor solution, the first ligand and the second ligand, Ir 0 With Ir δ+ The proportion of the two also showed regular changes. As the amount of the first ligand and the corresponding coordinated first metal precursor solution decreased, Ir 0 The proportion is gradually increasing.

[0111] 2. CO-SCR reaction performance test

[0112] 0.25 g of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively in the following manner:

[0113] The catalyst was placed in a fixed reactor with NO concentration of 400 ppm, CO concentration of 8000 ppm, O2 concentration of 5 vol.%, SO2 concentration of 100 ppm, N2 as the balance gas, and a space velocity of 10000 h -1 The nitrogen oxide conversion rate of the catalyst at different reaction temperatures was tested, and the results are shown in Table 2.

[0114] Before the formal performance test, all catalysts were pretreated. The pretreatment steps were as follows:

[0115] The catalyst was pretreated at 200°C in a 5 vol.% H2 gas flow (N2 as the balance gas) for 30 min to improve its catalytic activity. x ) conversion rate (μ NOx The calculation method is shown in Equation 1-1. The real-time changes in the specific gas concentration during the experiment were measured by Bruker Tensor II infrared spectroscopy. The product of complete catalytic reduction is N2.

[0116]

[0117] Table 2

[0118]

[0119] Table 2 shows the conversion rates of nitrogen oxides by the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 at different temperatures under the conditions of O2 concentration of 5 vol.% and SO2 concentration of 100 ppm. It can be seen that in the whole reaction process, the conversion rate of NO x The conversion rates are all about 0, indicating that the CO-SCR reaction catalytic activity of the molecular sieve support itself is extremely low, and the main active site is the Ir. The catalysts prepared in Examples 1 to 3 of the present invention have significant catalytic activity compared to that of Comparative Example 1, and as Ir 0 As the relative content increases, the conversion rate increases first and then decreases, showing a volcanic change. 0 With Ir δ+ The overall catalytic activity is the highest when the ratio is about 1:1, and the temperature at which the NOx conversion rate reaches 50% (T 50 ) is the lowest. When only the first ligand (Comparative Example 2) or the second ligand (Comparative Example 3) is used to coordinate with the metal Ir, the technical effect achieved by the embodiment of the present application cannot be achieved, which further indicates that the appropriate Ir 0 With Ir δ+ The relative content ratio of can effectively promote the increase in the number of active sites, thereby improving the catalytic performance of the catalyst.

[0120] 3. XRD test

[0121] Figure 1The XRD spectra of the catalysts prepared in Example 3 and Comparative Example 1 (where Ir@A represents Example 3 and Azeolite represents Comparative Example 1) are shown. Compared with the standard spectra, both Example 3 (i.e., Ir@A) and Comparative Example 1 (i.e., Azeolite) have characteristic peaks of type A molecular sieve, indicating that the carrier is successfully synthesized and the introduction of Ir does not destroy the molecular sieve structure. No obvious characteristic peak of Ir was observed in Example 3 (Ir@A), indicating that Ir is evenly dispersed on the carrier. The silicon-aluminum ratio and hydrothermal crystallization reaction time in the preparation process of Example 1, Example 2 and Example 3 are the same, and the type of molecular sieve carrier obtained is the same. After testing, the XRD spectra of the catalysts prepared in Example 1 and Example 2 are consistent with those in Example 3 and are not listed again.

[0122] 4. Catalyst morphology characterization

[0123] The catalysts prepared in Examples 1 to 3 and Comparative Examples 2 to 3 were subjected to TEM experiments. The sizes of 100 nanoclusters were counted in randomly selected areas, and a particle size distribution graph was drawn.

[0124] Figure 2 TEM image of the catalyst prepared in Example 2, Figure 4 The particle size distribution diagram of Ir nanoclusters in the catalysts prepared in Examples 1 to 3 and Comparative Examples 2 to 3. It can be seen from the TEM image that the Ir nanoclusters are relatively evenly dispersed on the molecular sieve carrier. It can be seen from the particle size distribution diagram that the sizes of Ir clusters are mainly in the two ranges of less than 0.8nm and 1 to 2nm. The proportion of clusters with a particle size of 1 to 2nm in the catalysts of Examples 1 to 3 gradually increases, and the proportion of clusters with a particle size of less than 0.8nm decreases successively. The particle size of the Ir clusters of the catalyst of Comparative Example 2 is mainly concentrated in the range of less than 0.8nm, indicating that its particle distribution is smaller and more concentrated. The Ir clusters of the catalyst of Comparative Example 3 are highly concentrated in the range of 1 to 2nm (the proportion is close to 90%), while the proportion of Ir clusters less than 0.8nm is relatively small. And as the proportion of the two ligands added is different, the proportion of clusters of different sizes is different, and the proportion of clusters of different sizes is similar to that of Ir. δ+ and Ir 0 The proportion trend (XPS results) is basically consistent.

[0125] 5. Stability test

[0126] 0.25 g of the catalyst prepared in Example 2 was tested at different SO2 concentrations as follows:

[0127] The catalyst was placed in a fixed reactor with NO concentration of 400 ppm, CO concentration of 8000 ppm, O2 concentration of 5 vol.%, SO2 concentration of 100 ppm, N2 as the balance gas, and a space velocity of 10000 h-1 , the nitrogen oxide conversion rate of the catalyst was tested at 250℃, and the results were as follows Figure 3 shown.

[0128] Before the formal performance test, all catalysts were pretreated. The pretreatment steps were as follows:

[0129] The catalyst was pretreated at 200℃ in 5vol.% H2 gas flow (N2 as balance gas) for 30min to improve its catalytic activity. x ) conversion rate (μ NOx )The calculation method is the same as shown in formula 1-1.

[0130] Figure 4 The results of the stability test of the catalyst prepared in Example 3 are shown in the figure. As can be seen from the figure, the activity of the catalyst is basically unchanged within 18 hours, and the catalytic activity is relatively stable.

[0131] 6. Catalyst activity test under different SO2 and O2 concentration ratios

[0132] 0.25 g of the catalyst prepared in Example 3 was tested at different SO2 concentrations as follows:

[0133] The catalyst was placed in a fixed reactor with NO concentration of 400 ppm, CO concentration of 8000 ppm, O2 concentration of 5 vol.%, SO2 concentration of 0, 100, 200, 300, 400 ppm, N2 as the balance gas, temperature of 250 ° C, and space velocity of 10000 h -1 The nitrogen oxide conversion rate of the catalyst at different reaction temperatures was tested, and the results are shown in Table 3.

[0134] Before the formal performance test, all catalysts were pretreated. The pretreatment steps were as follows:

[0135] The catalyst was pretreated at 200°C in a 5 vol.% H2 gas flow (N2 as the balance gas) for 30 min to improve its catalytic activity. x ) conversion rate (μ NOx )The calculation method is the same as shown in formula 1-1.

[0136] Table 3

[0137] <![CDATA[SO2 concentration (ppm)]]> 0 100 200 300 400 <![CDATA[O2:SO2]]> - 500 250 166.67 125 <![CDATA[NO x Conversion rate (%)]]> 12.54 80.06 75.26 61.25 41.38

[0138] Table 3 shows the NO of the catalyst prepared in Example 3 at different SO2 concentrations. x Conversion rate. In the presence of SO2, the activity of the catalyst is better than that without SO2. With the increase of SO2 concentration, NO xThe conversion of NO increases first and then decreases. x The conversion rate is the highest, indicating that the catalyst can maintain good activity under a suitable O2:SO2 ratio.

[0139] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A molecular sieve confined precious metal catalyst for CO-SCR denitration, characterized in that: The molecular sieve confined noble metal catalyst comprises a molecular sieve carrier and Ir metal nanoclusters loaded in the molecular sieve carrier through confined encapsulation.

2. The molecular sieve confined noble metal catalyst for CO-SCR denitration according to claim 1, characterized in that: The molecular sieve carrier is an A-type molecular sieve, an X-type molecular sieve or a Y-type molecular sieve; the loading amount of the Ir metal nanoclusters in the molecular sieve confined noble metal catalyst is 0.1-1wt.%; and the particle size of the Ir metal nanoclusters is ≤2nm.

3. The method for preparing a molecular sieve confined noble metal catalyst for CO-SCR denitration according to claim 1 or 2, characterized in that: The following steps are involved: Mixing a first metal precursor solution and a first ligand, and stirring to obtain a first mixed solution; Mixing the second metal precursor solution and the second ligand, stirring, to obtain a second mixed solution; Mixing a silicon source, an aluminum source, a base and a solvent, and stirring to obtain a molecular sieve precursor solution; The molecular sieve precursor solution is mixed with the first mixed solution, and stirred, and then the second mixed solution is added, and stirred to obtain a third mixed solution; The third mixed solution is subjected to a hydrothermal crystallization reaction, and after the hydrothermal crystallization reaction is completed, the mixture is centrifugally washed, dried, and calcined to obtain the molecular sieve confined precious metal catalyst for CO-SCR denitration; The first metal precursor solution and the second metal precursor solution are both Ir salt solutions.

4. The preparation method according to claim 3, characterized in that: The first ligand is a C1-6 straight-chain amine compound; the second ligand is an alkoxysilane containing a mercapto group or an amino group; the solute of the Ir salt solution includes at least one of iridium nitrate, iridium acetate and chloroiridic acid, and the solvent of the Ir salt solution is water.

5. The preparation method according to claim 3, characterized in that: The aluminum source includes at least one of sodium aluminate, boehmite, pseudo-boehmite, amorphous aluminum hydroxide powder and aluminum isopropoxide; the silicon source includes at least one of water glass, silica sol, silica gel and amorphous SiO2 powder; and the alkali is NaOH and / or KOH.

6. The preparation method according to claim 3, characterized in that: The Ir salt is calculated as Ir, and the molar ratio of the Ir salt to the first ligand in the first mixed solution is 1:3-8; the molar ratio of the Ir salt to the second ligand in the second mixed solution is 1:6-12.

7. The preparation method according to claim 3, characterized in that: The silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali is calculated as Na2O and / or K2O, and the Ir salt is calculated as Ir. The molar ratio of the silicon source, the aluminum source, the alkali and the Ir salt, the first ligand and the second ligand in the third mixed solution is 1-8:1:1-4:0.003-0.020:0.001-0.16:0.001-0.

24.

8. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal crystallization reaction is 80-120°C, and the time is 3-48 hours; the temperature of the drying is 80-120°C; the temperature of the calcination is 400-600°C, and the time is 4-8 hours, and the heating rate is 1-10°C / min.

9. Use of the molecular sieve confined noble metal catalyst for CO-SCR denitrification as claimed in claim 1 or 2 in catalyzing the selective reduction of nitrogen oxides by carbon monoxide in fixed source flue gas or mobile source tail gas.

10. The use according to claim 9, characterized in that The nitrogen oxides in the fixed source flue gas or the mobile source tail gas include NO; the fixed source flue gas and / or the mobile source tail gas also contain O2 and SO2.

Citation Information

Patent Citations

  • Molecular sieve packaged noble metal catalyst as well as preparation method and application thereof

    CN113559916A

  • Preparation of platinum nanocluster HA molecular sieve and application of platinum nanocluster HA molecular sieve in synthesis of 1, 2, 3, 4-tetrahydroquinoline

    CN115283007A

  • Preparation method of SSZ-39 molecular sieve shape-controllable packaged metal catalytic material

    CN115814847A

  • Molecular sieve confined monatomic catalyst as well as preparation method and application thereof

    CN116832855A

  • Silicon-aluminum zeolite molecular sieve packaged intermetallic compound CO-SCR catalyst as well as preparation and application thereof

    CN117324026A

Cited By

  • Preparation method and application of catalyst for synergistic removal of NOx and CO

    CN120920051A

  • A NO x Preparation method and application of CO synergistic removal catalyst

    CN120920051B

  • Catalyst for synergistically removing nitrogen oxides and carbon monoxide under high-oxygen condition as well as preparation method and application of catalyst

    CN121669304A

  • CO-SCR catalyst subjected to pre-sulfation treatment as well as preparation method and application of CO-SCR catalyst

    CN121755256A